Digital Rhetoric: Theory, Method, Practice - Eyman, Douglas (Digital Humanities, 2015)
A survey of a range of disciplines whose practitioners are venturing into the new field of digital rhetoric, examining the history of the ways digital and networked technologies inhabit and shape traditional rhetorical practices as well as considering new rhetorics made possible by current technologies